Projective identification and paranoid-schizoid position in Toni Morrison’s Home : a Kleinian reading - Yazdani, Saeed (Penerbit Universiti Kebangsaan Malaysia, 2022)
This article applies the Kleinian notion of projective identification on Morrison’s novel, Home. Based on the Kleinian notion of projective identification, there is a tendency in individuals to project the dark aspect of their lives on others. On the other hand, Paranoid-schizoid position is the starting point of the projective identification, originating from splitting of both ego and its objects. Toni Morrison’s novel Home, presents a disturbing narrative of childhood abuse, racial discrimination and impact of war on a traumatized individual. An attempt is made in the article to focus on an analysis of Morrison’s novel, Home, from the perspectives of the Kleinian projective identification, splitting, and schizoid-paranoid positions. The main question that the article poses is to what extent such concepts like projective identification and paranoid – schizoid position are applicable to the main characters, Frank Money in particular, in Toni Morrison’s Home. As a result, it can be concluded that under certain circumstances, Frank Money’s mental condition can be explored in terms of total shift from the past into the present; in addition to his emotional defenses, his social interaction with different institutions in the society has constructed his self because there have been different forces which he has confronted since his childhood.